The performance of the Pamong Belajar in the Learning Activity Center: In the Perspective of Leadership, Organizational Culture and Achievement Motivation - Paus, Julduz Ruland; Lumapow, Harol R.; Senduk, Johanis F.; Aditama, Mint Husen Raya (Journal of Nonformal Education, 2021)
The activities and existence of SKB as an educational institution in non-formal education units are a manifestation of the achievement of good corporate governance. This study aims to describe, predict and interpret the influence of leadership, organizational culture and achievement motivation on the performance of the Pamong Belajar at the Learning Activity Center (SKB) in North Sulawesi Province. The research approach used is quantitative with survey methods, while the hypothesis testing technique used is path analysis. There were at least 100 civil servants studying at 10 SKB and 15 districts / cities in North Sulawesi Province who were involved in this research. Research success indicators are measured based on 8 criteria contained in the Program Implementation Success Indicators (IKPP) and Institutional Success Indicators (IKK). From the results of the research analysis, it is found that the leadership characteristics of Pamong Belajar have a direct impact on organizational culture, achievement motivation and the performance of the Pamong Belajar SKB in North Sulawesi Province. However, there are interesting findings where achievement motivation can be a strong factor in the performance of the SKB Student Learning Association.